Prevalence of HIV status disclosure among young adolescents on antiretroviral therapy in Johannesburg, South Africa - Mhakakora, Tafadzwa; Mapungwana, Pheyiye; Chadyiwa, Martha (Orapuh Journal, 2025)
IntroductionDisclosure of HIV status is crucial for effective management and support among adolescents on antiretroviral therapy (ART).PurposeThis study aimed to assess the prevalence of HIV status disclosure and its associations with various factors among adolescents aged 10–14 years on ART.MethodsThis quantitative, descriptive study analysed secondary data from 281 adolescents aged 10–14 years on ART across thirteen public clinics. Participants were selected using convenience sampling. Key variables included disclosure status, gender, age, ART duration, attendance at support groups, clinic adherence, and viral load. Data were analysed using IBM SPSS (version 25), employing chi-square tests and t-tests, with a significance level set at p < .05.ResultsThe findings revealed that only 26.3% of participants had fully disclosed their HIV status. Full disclosure was significantly associated with clinic adherence (p = .002) and support group attendance (p < .05). However, no significant correlation was found between disclosure and viral load suppression (p = .886).ConclusionThe low prevalence of full HIV status disclosure underscores the urgent need for targeted interventions to enhance disclosure practices. Strengthening caregiver training and aligning health policies with the psychosocial development of adolescents are critical steps to improve health outcomes and provide effective support for this vulnerable population.